Legal Consequences Of Annulment Of A Prenuptial Agreement In Marriage Between Individuals Of Different Nationalities - Soraya, Joice; Althafzufar, Muhammad Ansy (PT. Hafasy Dwi Nawasena, 2024)
The author discusses the effects of annulment of prenuptial agreements in mixed marriages and how it affects the ownership of flats on land acquired after the marriage. Marriages between individuals of different nationalities often involve complex legal aspects, especially in the context of the annulment of prenuptial agreements. This research aims to investigate the legal consequences of annulment of prenuptial agreements in marriages between individuals of different nationalities. The text utilizes a normative legal approach conducted through literary research and a legislative approach. The study demonstrates the consequences of nullifying a prenuptial agreement in a mixed marriage, leading to joint ownership of assets acquired during the marriage and potentially affecting the ownership rights of apartment units on freehold land. Indonesian residents may lose their rights to an apartment unit (sarusun) in a freehold property if a prenuptial agreement was not made in a mixed marriage, as per domestic rules. After invalidating the prenuptial agreement, the Court should provide provisions to legally protect Indonesian citizens (WNI) regarding the ownership of apartment units on land with property rights status.